VIGITEC: uma nova ferramenta de comunicação em Vigilância Sanitária - Frazão, Ana Carolina; Dias, Cassius Tadeu de Lima; Fais, Cristina Quemelo Adami; Morais, Felipe Ambrosano de; Menezes, Helena Husemann; Fanni, Maria do Carmo Rezende; Pereira, Paulo Henrique Leuteviler; Neto, Plinio Cavalcanti de Albuquerque; Pegoraro, Priscilla Brandao Bacci; Baptista, Yunes Eiras; et al. (Revista Acadêmica GUETO, 2024)
Projeto